Effect of copper diffusion on photovoltaic characteristics of CuGaSe2-GaAs cells - Dzhafarov, TD; Sadigov, MS; Bacaksiz, E; Oren, D; Karabay, I (ELSEVIER SCIENCE BV, 1998)
CuGaSe2-GaAs heterojunctions were fabricated by fast evaporation of polycrystalline CuGaSe2 from a single source on n-type GaAs substrates. The best CuGaSe2-GaAs photocell (without an antireflective coating) exhibited an efficiency of 11.5%, J(sc) = 32mA/cm(2), V-oc = 610 mV and FF = 0.60. The spectral distribution of photosensitivity of CuGaSe2-GaAs junctions extends from 400 to 900 nm. The CuGaSe2 films were characterized by X-ray diffraction (XRD) and scanning electron microscope (SEM) techniques. XRD analysis indicated that the thin films were strongly oriented along the (112) plane. SEM studies of CuGaSe2 films showed nearly stoichiometric composition with grain size about 1-2 mu m. The energy dispersive X-ray spectroscopy (EDX) analysis of Cu concentration distribution in n-type GaAs showed that Cu diffused from the film into n-type GaAs during the growth process resulting in formation of the latent pn homojunction in substrate. The diffusion coefficient of Cu in GaAs at growth temperature (520 degrees C) estimated from EDX measurements was 6 x 10(-8) cm(2)/s. (C) 1998 Elsevier Science B.V. All rights reserved.
Keywords: copper diffusion; photovoltaic characteristics; CuGaSe2-GaAs cells; Energy & Fuels; Materials Science; Physics